2012
DOI: 10.1021/jp302847h
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of CoO Nanocrystals and a Single Crystal Probed by Resonant X-ray Emission Spectroscopy

Abstract: We have performed 2p X-ray absorption (XAS) and 2p3d resonant X-ray emission (RXES) experiments on a CoO bulk single crystal as well as on 4.2 nm CoO nanocrystals. The single crystal data were measured with linearly polarized incident X-rays in the scattering and perpendicular to the scattering plane. An unprecedented total experimental resolution of 100 meV allowed the first Xray observation of the CoO 4 T 1g ( 4 F) manifold that occurs 120 meV above ground state. Detailed theoretical modeling was performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(110 citation statements)
references
References 54 publications
10
100
0
Order By: Relevance
“…The 0.870 and 2.3 eV peaks are in agreement with x-rays but the 1.84 eV excitation was not resolved with non-resonant xrays and is forbidden in the dipolar approximation, however it has been reported in other optical and x-ray studies such as RIXS and EELS that are sensitive to dipole forbidden cross sections. 38,[43][44][45][46][47] This result highlights the point that the 1.84 ±0.03 eV excitation is dipole forbidden and confirms our claim that we are sampling a quadrupolar matrix element in our neutron scattering experiments.…”
Section: A Comparison With Inelastic X-rays and Optical Techniquessupporting
confidence: 87%
“…The 0.870 and 2.3 eV peaks are in agreement with x-rays but the 1.84 eV excitation was not resolved with non-resonant xrays and is forbidden in the dipolar approximation, however it has been reported in other optical and x-ray studies such as RIXS and EELS that are sensitive to dipole forbidden cross sections. 38,[43][44][45][46][47] This result highlights the point that the 1.84 ±0.03 eV excitation is dipole forbidden and confirms our claim that we are sampling a quadrupolar matrix element in our neutron scattering experiments.…”
Section: A Comparison With Inelastic X-rays and Optical Techniquessupporting
confidence: 87%
“…61 Because the CT feature has a low intensity and is observed at relatively high energies, it will not affect the d–d excitation features in the first 6 eV as discussed in this article. 30,62 Also, the L 3 XAS reveals no substantial CT shoulder on the high-energy-side of the L 3 edge, typical for systems in which CT plays a large role. 62 The omission of antibonding Cr–O CT effects in the simulations is thus justified and further substantiated by an excellent match of the calculations with both experimental XAS and RIXS data.…”
Section: Discussionmentioning
confidence: 93%
“…For a more detailed, basic description of the parameters, we refer to previous work. 18,30 For all simulated spectra, an appropriate Boltzmann-population weighted ground state contribution is considered.…”
Section: Computational Detailsmentioning
confidence: 99%
“…We frankly admit that in our own previous RIXS work, we failed to properly discuss potential photoreduction processes. However, we believe that much of the original observations hold due to the fortuitous circumstance of having worked on Co 2+ ions [18,[82][83][84], where it is in general observed that metal 2+ ions are the final product of photoreduction processes.…”
Section: Introductionmentioning
confidence: 95%